1986
DOI: 10.1002/art.1780291108
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in synovial fluid and tissue from patients with juvenile rheumatoid arthritis

Abstract: Synovial fluid (SF) and synovial tissue from 10 patients with juvenile rheumatoid arthritis were examined. The SFs were heterogeneous with respect to the degree of complement activation. Quantification of C3dg and the terminal complement complex revealed a positive correlation between activation of the early and the late parts of the cascade in all patients. The amount of C‐reactive protein and the number of white blood cells in the SF correlated significantly with the degree of complement activation. Weak dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Taking into account the molecular size of the C1q-C4 complexes and the ratio between synovial fluid concentration and plasma concentration, it is most likely that C1q-C4 complexes are produced locally in the joint, and that the plasma levels measured in RA are the result of spillover. This would explain the higher C1q-C4 plasma levels in patients with active disease, since complement activation in the joint is higher in these patients (5,6,38).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Taking into account the molecular size of the C1q-C4 complexes and the ratio between synovial fluid concentration and plasma concentration, it is most likely that C1q-C4 complexes are produced locally in the joint, and that the plasma levels measured in RA are the result of spillover. This would explain the higher C1q-C4 plasma levels in patients with active disease, since complement activation in the joint is higher in these patients (5,6,38).…”
Section: Discussionmentioning
confidence: 97%
“…For example, levels of complement proteins are depressed in the synovial fluid of patients with RA, reflecting consumption of complement. Moreover, elevated levels of complement cleavage products, such as sC5b-9, C3a, Bb, and C1inh-C1s complexes, have been observed in synovial fluid (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In rheumatoid arthritis elevated levels ofTCCs have been found in synovial fluid and in plasma Mollnes & Paus, 1986;Morgan et al, 1988b) and the MAC has been localized in rheumatoid synovium (Sanders et al, 1986a). In rheumatoid joints release of inflammatory mediators including arachidonic acid metabolites and cytokines into synovial fluid has been demonstrated and a role of these mediators in the causation or propagation of inflammation suggested (Hopkins et al, 1988).…”
Section: Rheumatological Diseasesmentioning
confidence: 99%
“…Complement levels in the synovial fluid of RA patients can be lower than those in controls because of local consumption (17). Complement activation products such as sC5b-9, Bb, C3a, and C1 inhibitorC1s and C1q-C4 complexes have been shown to be increased in synovial fluid (18)(19)(20)(21)(22), and complement depositions in synovial tissue from RA patients can be visualized by immunohistochemistry (23). Recent genetic association studies have indicated that complement (C5 in one previous study [24]) may be involved in the pathogenesis of human RA.…”
mentioning
confidence: 99%